Pump-probe study of the formation of rubidium molecules by ultrafast photoassociation of ultracold atoms - McCabe, D; England, D; Martay, H; Friedman, M; Petrovic, J; Dimova, E; Chatel, B; Walmsley, I (2009)
An experimental pump-probe study of the photoassociative creation of translationally ultracold rubidium molecules is presented together with numerical simulations of the process. The formation of loosely bound excited-state dimers is observed as a first step toward a fully coherent pump-dump approach to the stabilization of Rb2 into its lowest ground vibrational states. The population that contributes to the pump-probe process is characterized and found to be distinct from a background population of preassociated molecules. © 2009 The American Physical Society.